HUBUNGAN INDEKS GIZI SEIMBANG DENGAN KEJADIAN OBESITAS PADA REMAJA DI KOTA DEPOK - Rana Nurfitri (2022)
Healthy Eating Index (HEI) is an instrument or tool for measuring the suitability of a subject's food consumption against the recommended meal portion. The Balanced Nutrition Index refers to the Balanced Nutrition Guidelines (PGS) by looking at the portion and type of food consumed. If the subject's IGS score reaches the maximum, this indicates that the quality of the subject's food consumption is good and in accordance with the guidelines recommended. Poor diet quality does not take into account the excessive amount of nutrients that enter the body, as well as the variety of food consumed. Obesity is also influenced by dietary factors, where the high amount of energy consumed and food consumption does not meet dietary recommendations, can reduce the quality of food consumption. This study aims to determine the relationship between a balanced nutrition index and the incidence of obesity in adolescents in Depok City. This study used a cross-sectional study design which was taken with a simple random sampling technique of 164 respondents. Data was collected by filling out questionnaires and FFQ (Food Frequency Questionnaire) interviews and then using the chi-square test. Based on the results of statistical tests, there is no relationship between the balanced nutrition index of carbohydrate food components (p=0,497); (p=0,301), animal source (p=0,535);(p=1,000), vegetable source (p=1,000);(p=0,062), vegetable food component (p=0,348);(p=0,644), fruit food component (p=0,519);(p=1,000), and dairy food component (p=0,529);(p=0.659) with the incidence of obesity in male and female adolescents. There was no relationship between a balanced nutrition index and the incidence of obesity in adolescent boys and girls (p=0,745);(p=0,000).